Model checking requirements written in a controlled natural language - BARZA, Sérgio (2016)
Software Maintainability (SM) has been studied since it became one of the key componentes of the software quality model accepted around the world. Such models support researchers and practitioners to evaluate the quality level of his systems. Therefore, many researchers have proposed a lot of metrics to be used as SM indicators. On the other hand, there is a suspicious that using SM metrics on industry is different from the academic context. In this case, practitioners do not adopt the metrics proposed/used by academia. Consequently, the goal of this research is to investigate the SM metrics adoption and applicability scenario on the Brazilian industrial context. This study will allow confirming if the practitioners use the SM metrics proposed by academics around the globe or if they propose their own metrics for SM measurement. As empirical method for data assessment, we used survey, divided in two steps. The first one was focused in gathering information that allowed us to design a specific scenario about the use and applicability of SM metrics. To achieve this goal, it was chosen, as research instrument, semi-structured interviews. The next step focused in a more general scenario, compassing the Brazillian software production industrial context. An online questionnaire was used as research instrument. Practitioners with different positions in several companies participated of this work. Data from requirements engineers, quality analysts, testers, developers and project managers were collected. 7 software companies participated in the first part of the study and 68 valid answers were collected on the second moment, resulting in 31 SM metrics listed. The results showed us that about 90% of the companies perform maintenance on their software products. However, only 60% confirms using maintainability metrics, resulting in a discrepancy regarding software maintenance vs SM metrics. Nearly half of the companies researched have used well-defined processes to collect these metrics. Nevertheless, there are those that do not have any formal methodology. Instead of it, they have used SM metrics that best fit to the needs of a specific project. The conclusions of this study point to an issue that is nothing new in the academic researchers around the world. Many of the academics results conducting, mainly, in the universities, are not coming to the software industries and this fact is also a truth when the subject is software maintenance. The results of this research may lead to discussions on how SM metrics are being proposals nowadays.